Burkina Faso : Joint Staff Advisory Note on the Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Burkina Faso has set up ambitious developmental goals and outlined policies and reforms to reach these goals under the Strategy for Accelerated Growth and Sustained Development (SCADD). It is recognized that poverty alleviation is a long-term challenge, and there is greater scrutiny of the implementation process to ensure effectiveness. It will be important to increase the priority given to good governance, accountability, and inclusive growth. The main objective is to achieve strong and sustained economic growth. The Executive Directors encourage the government to address the shortcomings identified.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet